2002
DOI: 10.1002/mrd.10043
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic pigs expressing human decay‐accelerating factor regulated by porcine MCP gene promoter

Abstract: Porcine membrane cofactor protein (pMCP) is abundantly expressed throughout the body with particularly strong expression on the vascular endothelia. Previous studies demonstrated that the promoter of the pMCP gene induced efficient expression of a human complement regulatory protein, decay-accelerating factor (DAF; CD55), in transgenic mice. In the present study, we tried to produce transgenic pigs with two hybrid genes, 0.9/hDAF and 5.4/hDAF, which were composed of human DAF (hDAF) gene regulated under pMCP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Activation of coagulation and complement cascades also occurs following xenotransplantation. Transgenic pigs which express human complement genes such as human decay accelerating factor (hDAF), a human complement regulatory protein [44][45][46] and CD59 [47], as well as human membrane co-factor [48] have also been produced. In-vitro CD59 producing porcine cells strongly resist from the exposure of human complement and anti-porcine antibody [47], although ex vivo experimentation shows only partial protection in the case of porcine lungs perfused with human blood [49].…”
Section: Advances In Xenotransplantation Of Porcine Tissuesmentioning
confidence: 99%
“…Activation of coagulation and complement cascades also occurs following xenotransplantation. Transgenic pigs which express human complement genes such as human decay accelerating factor (hDAF), a human complement regulatory protein [44][45][46] and CD59 [47], as well as human membrane co-factor [48] have also been produced. In-vitro CD59 producing porcine cells strongly resist from the exposure of human complement and anti-porcine antibody [47], although ex vivo experimentation shows only partial protection in the case of porcine lungs perfused with human blood [49].…”
Section: Advances In Xenotransplantation Of Porcine Tissuesmentioning
confidence: 99%
“…Recently, we produced transgenic pigs expressing the human decay-accelerating factor (DAF,CD55) and demonstrated that their cells resist human complement attack (Murakami et al, 2002). We also produced transgenic pigs expressing N-acetylglucosaminyltransferase III (GnT-III), which remodels the sugar chain biosynthesis on the cell surface, and reduces not only the ␣1,3Gal epitopes but also other xenoreactive antigens such as Hangautziu-Deicher (H-D) antigen (Miyagawa et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, trials designed to overcome hyperacute rejection by the expression of DAF in a xenograft have enabled the down-regulation of NK cell-mediated acute vascular rejection without realizing it (7). Further studies are currently in progress to clarify the DAF-NK interaction.…”
Section: Discussionmentioning
confidence: 99%